(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The question of choice of methods of teaching for the high-quality mastering of theoretical knowledge’s, acquisition of practical abilities and skills is explored by the students of educational establishments of artistically-pedagogical education on a course "Decoratively-applied art”.